Retraction notice to “Incorporation of Mn2+ and Co2+ to TiO2 nanoparticles and the performance of dye-sensitized solar cells” [Appl. Surf. Sci. 283 (2013) 975–981, (S0169433213013664), (10.1016/j.apsusc.2013.07.055)] - Shalan, A. E.; Rashad, M. M. (Applied Surface Science, 2024)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal). This article has been retracted at the request of the Editor-in-Chief due to concerns about the integrity of the research reported. Concerns were raised about the reliability of the data presented in several of the figures (detailed on Pubpeer), whereby unexpected similarities were observed in the depiction of different experimental samples. Specifically, these similarities were observed between the samples presented in Figure 4, Figure 6, between Figures 3A & 3B, and between Figures 3A & 3C. Additionally, there is unexpected similarity observed between Figure 1 of the current article and Figure 1 in the Journal of Alloys and Compounds article “The structural, optical, magnetic and photocatalytic properties of transition metal ions doped TiO2 nanoparticles” by Rashad et al. [1], on which the authors of the current article appear as first and last author. The authors were contacted for comment about the above-mentioned concerns but were unable to provide a suitable explanation for how the similarities came about. The Editor in Chief has therefore lost confidence in the reliability of the findings presented in this article as a whole. In light of the above, the Editor in Chief believes that the most responsible course of action is to retract the paper. Apologies are offered to the readers that this was not detected sooner.
CRIS-Team Scopus Importer:2024-12-13